2011
DOI: 10.3109/01612840.2011.579689
|View full text |Cite
|
Sign up to set email alerts
|

Children's View of a Major Depression Affecting a Parent in the Family

Abstract: This study aims to elucidate, from the children's perspective, the meaning for family life of a parent suffering a major depression disorder. Eight children and young adults were interviewed. Phenomenological-hermeneutic analysis generated two themes: (1) "Being a rescuing observer" with the subthemes, "Being attentive" and "Being considerate," and (2) "Being a frustrated observer" with the subthemes, "feeling discomfort" and "being out of it." Children's lives alternate between responsibility and loneliness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Hedman et al. found that anxiety and concern for the depressed parent also affected children after they had moved out. In 2010, an amendment to the Norwegian Health Personnel Act stated that health personnel are obliged to establish whether the patient has children under the age of 18 and to further ensure that the child's need for information and follow‐up is safeguarded .…”
Section: Discussionmentioning
confidence: 99%
“…Hedman et al. found that anxiety and concern for the depressed parent also affected children after they had moved out. In 2010, an amendment to the Norwegian Health Personnel Act stated that health personnel are obliged to establish whether the patient has children under the age of 18 and to further ensure that the child's need for information and follow‐up is safeguarded .…”
Section: Discussionmentioning
confidence: 99%
“…The children of parents with mental illness often take responsibility for the parenting role; they become caregivers for the parent and younger siblings, particulary during their parent's bad periods (54)(55)(56)(57)(58). The children care for their parents by being considerate (49), comforting them and avoiding doing things that cause upset (14,48,59). To reduce family stress, the children share humour, help around the house and by just 'being there' or being supportive in any way not being a burden (48,(59)(60)(61).…”
Section: Metasynthesismentioning
confidence: 99%
“…Additionally, there were no significant differences in perceived family functioning between patients and their spouses for all dimensions of FAD, suggesting that patient perception was not significantly distorted by their depression, and that depressed patients and their spouses all perceived impaired family functioning when one family member suffered from a first episode of major depression. A previous study showed differences in perceived family functioning between adolescents with depression and their parents in a Western sample, with depressed adolescents perceiving poorer family functioning than their parents (Hedman Ahlström et al ., ). Another study found that depressed Japanese patients saw family functioning more positively than their family members did (Koyama et al ., ).…”
Section: Discussionmentioning
confidence: 97%